A mitochondria-targeted fluorescent probe based on fluorescein derivative for detection of hypochlorite in living cells. (January 2018) - Lv, Jing; Chen, Yahui; Wang, Fang; Wei, Tingwen; Zhang, Zhijie; Qiang, Jian; Chen, Xiaoqiang
Abstract: In the present study, a mitochondria-targeted fluorescent probeFL based on fluorescein derivative for hypochlorite sensing was designed and synthesized. The probeFL showed highly selective to HOCl among various reactive oxygen/nitrogen species. With the increasing amount of HOCl from 0 to 50 μM, a linear correlation between the fluorescence intensity ofFL at 530 nm and the concentration of HOCl was found. The detection limit is calculated to be 0.068 μM. Furthermore, the probe demonstrated a perfect mitochondria targetable ability and it was successfully applied to image mitochondrial HOCl in living HeLa cells. The success of subcellular imaging indicated that the mitochondria-targetable probeFL might be further used to investigate biological functions and pathological roles of HOCl at organelle levels. Graphical abstract: Highlights: A highly selective fluorescent probe based on fluorescein aldehyde is developed for HOCl detection. The probe exhibited a perfect mitochondria targetable ability. The probe can be used to detect mitochondrial HOCl and monitor the MPO-catalyzed HOCl generation in living cells.